Conventional Processing Affects Nutritional and Antinutritional Components and In Vitro Protein Digestibility in Kabau (Archidendron bubalinum) - Aprilia Fitriani; Umar Santoso; Supriyadi Supriyadi (International Journal of Food Science)
Kabau, an unexplored crop, was analyzed to determine its nutrition and antinutrition components and in vitro protein digestibility (IVPD). Some conventional processes, such as steaming, frying, and boiling, were carried out to study their effect. The results indicated that all of the techniques reduced carbohydrate content. Frying significantly increased the fat content of Kabau and reduced other nutritional components. In general, all the methods significantly reduced phytic acid, tannin, and trypsin inhibitors, as much as 94.95–96.26%, 20–35%, and 89.22–92.88%, respectively. The reduction of antinutritional components resulted in higher IVPD on boiled and steamed Kabau, 69.47% and 61.48%, respectively.